Is Shakespeare still relevant and important today and should his works be taught in schools in all countries, not just Britain? - Salam Hussein Yahya; Ali Baram Mohammed (The Scientific Journal of Cihan University– Sulaimaniya, 2017)
“Shakespeare reveals a different face to different cultures and different people at different times,” explained Bruce Smith, Dean’s Professor of English and professor of theatre at University of southern California.This study investigates the immortality of Shakespeare in twenty-first-century. William Shakespeare, as known to the entire universe has left a great impact upon most of the people in the world. His masterpieces are ubiquitous and individuals from every part of the world are reading and renewing them. However, when it comes to schools and their syllabus, each country has their own methods and opinions whether or not to teach Shakespeare in their schools. Therefore, the aim of this study is to figure out people’s views and perceptions towards this topic. The study is carried out amongst individuals from as diverse backgrounds as possible and the questions encompassed all the aspects of Shakespeare’s works. To what extend do the interviewees agree that Shakespeare is still relevant and his works have to be taught in every part of this universe.